Light Activated Electrochemistry: Light Intensity and pH Dependence on Electrochemical Performance of Anthraquinone Derivatized Silicon - Yang, Y.; Ciampi, Simone; Choudhury, M.; Gooding, J. (American Chemical Society, 2016)
We seek to understand how the thermodynamics and kinetics of anthraquinone-containing self-assembled monolayer on silicon electrodes are affected by two key experimental variables: the intensity of the light assisting the anthraquinone/anthrahydroquinone redox process and the local solution environment. The substrates are chemically passivated poorly doped p-type silicon electrodes. The study presents a strategy for the selective modulation of either the anodic or the cathodic process occurring at the interface. Cyclic voltammetry studies showed that unlike for a proton-coupled electron transfer process performed at metallic electrodes, for the redox reaction of the anthraquinone unit on a silicon electrode it becomes possible to (i) selectively facilitate only the oxidation process by increasing the electrolyte pH or (ii) at a given pH value to increase the illumination intensity to anodically shift the onset of the reduction step only but leave the oxidation process thermodynamic unchanged. A model concerning the proton coupled electron transfer mechanism was proposed, where the electron transfer is the rate-determining step for the anthraquinone reduction while a deprotonation step is the rate-determining event for the anthrahydroquinone oxidation on poorly doped illuminated p-type silicon.